Dealing with bullying among students in secondary schools: Sources of teachers' self-efficacy - Lee, Jun Choi (2015)
Scant attention has been paid to teachers’ self-efficacy regarding bullying and what actually are their ability when they deal with this type of problem, particularly in Malaysia.There is also relatively little information about sources that have an impact on teacher self-efficacy regarding dealing with bullying in school, in the local context or probably in the international arena. The source of influence is predicted to be from behavior factors (i.e. mastery experience); environmental factors (i.e. vicarious experience, verbal persuasion, and contextual climate) and personal factors (i.e. demographic information, and psychological arousal).The purpose of this study was to identify the overall source of influence that contributes to teacher self-efficacy and identify which sources of influence are significant predictors of teacher self-efficacy in dealing with bullying among students in secondary schools.This quantitative research utilizes a correlation method in order to examine the relationship between various sources of influence and teacher sense of efficacy when dealing with bullying among students in secondary schools.Based on the standardized regression coefficients (βs) indices of direct effects of each predictor variable on teacher self-efficacy in dealing with bullying among students, Mastery Experience contributed the highest direct effect or influence on teacher self efficacy in dealing with bullying among students, followed by Verbal Persuasion and Contextual Climate. Although there is no documented record of local research that examine the sources of influence on teacher self-efficacy in dealing with bullying among students, one clear finding that arises from this study is that, mastery experience and verbal persuasion are prominent predictors of teacher self-efficacy in dealing with bullying among students in secondary schools.It is recommended that teacher preparation or teacher developmental programs regarding the issue of bullying among students in secondary schools, explicitly address these two influences with specific types of training and educational experiences that focus on mastery building through cognitive and meta cognitive strategies, cultivating self-regulation competencies, and establishing a social support system.